Avaliação de um programa de mediação de conflitos: a experiência da Imed - Passo Fundo - Oliveira, Luiz Ronaldo Freitas de (Universidade do Vale do Rio dos Sinos, 2010)
The aim of this study was to evaluate the Conflict Mediation Program of IMED, Passo Fundo, analyzing its process, and identifying characteristics and interventions used to promote or not the establishment of agreements. A qualitative study was conducted and the exploratory strategy was adopted. The procedure of Multiple Case Studies was used (Yin, 2005). Participants were addressed by the Forum of Passo Fundo for attendance in that program, aimed at solving some form of litigation related to family disputes over custody and / or regulation of visits. There were four case studies, each one composed by the parents and the children involved, and who agreed to participate. Data were collected at different times. In the first stage, the selected cases were assisted by the Program for Conflict Resolution of IMED. This service was conducted by another team than the one that integrates the researcher. The interviews were recorded, with permission, and transcribed. In the second stage, four months after the end of the mediation process, when it was successful in terms of getting agreement between the participants, they were interviewed again in order to assess whether the agreement was kept. The data were analyzed according to the method of theoretical propositions by Yin (2005). The main findings pointed to a positive outcome of the mediation process in terms of the agreement between the participants, recovery of dialogue and communication. Interventions focused on the present and future, and in overcoming the conflict were most successful.
Keywords: Mediação; Conflitos familiares; Programa de mediação; Mediation; Family conflict; Mediation program; ACCNPQ::Ciências Humanas::Psicologia